Konsep Dasar Kepemimpinan Islam dalam Menumbuhkan Jiwa Kepemimpinan pada Siswa di SMPIT Bina Benuanta Tanjung Selor - Abdul Arif (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
That students or students are part of the nation's future youth who are the milestones for future progress. Forming a student's character can start with the importance of a student learning about leadership. The leadership of Rasulullah Muhammad SAW is a leadership model that can be implemented in organizations. Islamic leadership is the entire process of influencing, encouraging, inviting, moving and guiding other people in the work process to think and act in accordance with applicable rules in order to achieve goals set based on the values ​​of the Al-Qur'an and Sunnah. Leadership in Islam is very important because it functions to create public problems and realize equal prosperity for all citizens. The data sources in this research are primary and secondary data. This research is qualitative research. This research was conducted at the SMPIT Bina Benuanta Tanjung Selor school by providing material exposure to learners or students with the hope of forming and encouraging a culture of quality Islamic education in understanding and developing Islamic leadership practices so that quality education, with integrity and oriented towards Islamic values, is realized.